Avaliação da qualidade ambiental da água e sedimento de quatro mananciais de abastecimento público do estado de Goiás - Moura, Laís Simões de (2014)
The sources of supply must have its sheltered water for contamination in obedience to CONAMA Resolution 357/2005, which regulates the standard of quality that water for public supply should have to be used by the population, after some treatment. However, the fact that the rivers act as the last destination of contaminants it is necessary analyzes the sediment to the complete assignment quality water for consumption because the contaminats coming from air, land and even their own water. Thus, the aim of this study was to evaluate the environmental quality of four sources of supply - Ribeirão Sozinha, Córrego Água Branca, Córrego dos Macacos e Ribeirão Arrozal, - located in the metropolitan area of Goiânia / GO. The study was divided into four sections. The first chapter discussed the importance of sediment analysis in the discussion of water quality and found that over a period of ten years, the number of published studies that analyzed the sediment is small, but the numbers of related publications have increased each year. The second chapter evaluated the quality of water sources in a holistic mannerclassifying them according to the results of applying a Rapid Assessment Protocol Diversity of Habitats and some physico-chemical analysis. It was noted that these rivers are suffering from anthropic action and it can compromise the water quality of them. The third chapter measured the quality of the rivers from the results obtained from analyzes of temperature, pH, Eh, conductivity, turbidity, DO, BOD, COD, organic matter, total nitrogen, total phosphorus, total suspended solids, total solids, total dissolved solids, total coliform and Escherichia coli in water and sediment test results of pH, Eh, moisture, organic matter and sediment grain size. Thus, it was possible to evaluate the four rivers in the category of class II freshwater according to relevant legislation and, considering these parameters, they have good quality and can continue to be used for this purpose. The fourth chapter evaluated the quality of water sources in relation to the concentration of six metals in water and sediment. Concentrations of Cd, Cr and Cu were found in the water; and concentrations of Cd, Cr and Ni in the sediment disagreement the limits established by law. Thus, it was concluded that these sources, even showing signs of anthropogenic physical deterioration, still offer quality water. However, it is necessary to the continuous monitoring of this quality in order to avoid future problems to the population who depend on this water resource.